Mutations in presenilin 2 and its implications in Alzheimer’s disease and other dementia-associated disorders - Cai Y (Dove Medical Press, 2015)
Yan Cai,1 Seong Soo A An,1 SangYun Kim2 1Department of Bionano Technology, Gachon Medical Research Institute, Gachon University, 2Department of Neurology, Seoul National University College of Medicine, Seoul National University Bundang Hospital, Seongnam-si, Gyeonggi-do, South Korea Abstract: Alzheimer’s disease (AD) is the most common form of dementia. Mutations in the genes encoding presenilin 1 (PSEN1), presenilin 2 (PSEN2), and amyloid precursor protein have been identified as the main genetic causes of familial AD. To date, more than 200 mutations have been described worldwide in PSEN1, which is highly homologous with PSEN2, while mutations in PSEN2 have been rarely reported. We performed a systematic review of studies describing the mutations identified in PSEN2. Most PSEN2 mutations were detected in European and in African populations. Only two were found in Korean populations. Interestingly, PSEN2 mutations appeared not only in AD patients but also in patients with other disorders, including frontotemporal dementia, dementia with Lewy bodies, breast cancer, dilated cardiomyopathy, and Parkinson’s disease with dementia. Here, we have summarized the PSEN2 mutations and the potential implications of these mutations in dementia-associated disorders. Keywords: mutations in presenilin 2, Alzheimer’s disease